Performance of fast and ultrafast T2-weighted MRI sequences for common cerebral lesions in children - Gräfe, Daniel; Anders, Rebecca; Frahm, Jens; Voit, Dirk; Simion, Stefan-Horia; Merkenschlager, Andreas; Hirsch, Franz Wolfgang (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
The use of fast and ultrafast T2-weighted sequences allows for low-motion-artifact imaging of the cerebrospinal fluid spaces and can thus avoid sedation in young children for cranial MRI (cMRI). It is still unclear to what extent these sequences can also depict other common cerebral findings in children. The aim of the study was to compare the potential delineation of common intracranial findings in pediatric cMRI with two fast and one ultrafast T2-weighted sequences.Children who had undergone a single-shot spin-echo and gradient echo sequence, as well as an ultrafast volume coverage (VC) sequence, in addition to a standard T2-weighted fast spin-echo (FSE) sequence as reference were retrospectively included. Visualization of findings was assessed using a Likert scale from 0 to 3. Differences between groups of findings were quantified using a Kruskal-Wallis test.284 findings in 126 patients (median age: 10.6 years, interquartile range: 5.1 to 15.0 years) were analyzed. Overall, in fast T2-weighted sequences, the percentage of visible (score 2 or 3) findings was between 60% and 100%. There was little difference between the two fast sequences and the ultrafast VC.Ultrafast VC as compared to conventional fast sequences allows for almost the same discrimination of common neuropediatric pathologies but at seven times the speed. Although not an equivalent substitute for T2 FSE in parenchymal findings, it can contribute to triage at little expense and thus reduce the burden on both patients and staff.
Keywords: brain; sedation; MR-imaging; artifacts